Performance Evaluation of a Modified Carrier Sense Multiple Access with Collision Detection Protocol - Kabir, Shamima (2005)
Using Carrier Sense Multiple Access with Collision Detection (CSMMCD), Ethernet Local Area Networks (LANs) suffers from capture effect in packet loss. As a result of capture effect, some nodes may be locked-out of using the medium for a period of time. Hence, CSMAICD based Ethernet is unsuitable for real-time multimedia traffic. It does not guarantee delay bound, behaves poorly under heavy load conditions. To overcome these shortcomings and enhance performance of CSMAKD based LAN, three new concepts are added to the conventional CSMMCD. Firstly, each node in the LAN has a finite buffer. A node competes for access to the medium after its buffer is full. It will transmit all packets in the buffer if access is permitted. To minimize the waiting delay of packets in the buffer prior to transmission, a time-out period is set, beyond which a node tries to transmit considering its buffer is full.Due to buffer, the number of nodes trying to transmit at a time is reduced, thereby collision rate is reduced. Capture effect, locked-out probability, bandwidth loss and backoff delays are also reduced. To support all types of traffic (mainly real-time traffic), the optimum buffer size obtained is 10 packetsibuffer. Using this buffer, multimedia traffic can be sent in a streamed fashion within a delay bound. Secondly, the maximum retransmission attempt limit and backoff limit are reduced to 10 and 8 times respectively to guarantee a tolerable delay for multimedia applications. A new special-jamming signal is introduced. It gives transmission priority to the node that already has finished its maximum retransmission attempt. This prevents packet loss and quality degradation of received normal data traffic and multimedia traffic. The final one is the priority scheduler, which is activated when multiple nodes send the special-jamming signal at a time. It gives permission to the node having either the lowest timestamp or the smallest source address (SA) to transmit while other nodes wait until their access is permitted accordingly. The proposed protocol is based on bus topology for a single channel LAN. Throughput, transmission efficiency, average delay and percentage of collision of the proposed network is evaluated against number of nodes, bus length and offered load within two environments, i.e. Fast Ethernet and Gigabit Ethernet. The results show significant performance improvement. Throughput, transmission efficiency are increased more than 10% in average. On the other hand, average delay and percentage of collision are reduced to less than 2 ms and 3.5% respectively compared to the conventional CSMA/CD based LAN.